2022
DOI: 10.3390/polym14224947
|View full text |Cite
|
Sign up to set email alerts
|

The Applications of Ferulic-Acid-Loaded Fibrous Films for Fruit Preservation

Abstract: The aim of this study was to develop a novel ultrathin fibrous membrane with a core–sheath structure as an antioxidant food packaging membrane. The core–sheath structure was prepared by coaxial electrospinning, and the release of active substances was regulated by its special structure. Ferulic acid (FA) was incorporated into the electrospun zein/polyethylene oxide ultrathin fibers to ensure their synergistic antioxidant properties. We found that the prepared ultrathin fibers had a good morphology and smooth s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
70
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 92 publications
(71 citation statements)
references
References 94 publications
1
70
0
Order By: Relevance
“…Additionally, nanofiber membranes prepared by electrospinning also have special qualities, such as high porosity, large specific surface area, controllable fiber structure, and easy recovery. As shown in Figure 1 , electrospinning equipment is primarily made up of components including a high-voltage power source, a propulsion pump, a syringe, a spinneret, and a collection apparatus [ 4 , 5 , 6 ]. The high voltage applied at the spinneret tip is used as the viscous electrospinning solution in the spinneret and is extruded at a steady rate to be charged.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, nanofiber membranes prepared by electrospinning also have special qualities, such as high porosity, large specific surface area, controllable fiber structure, and easy recovery. As shown in Figure 1 , electrospinning equipment is primarily made up of components including a high-voltage power source, a propulsion pump, a syringe, a spinneret, and a collection apparatus [ 4 , 5 , 6 ]. The high voltage applied at the spinneret tip is used as the viscous electrospinning solution in the spinneret and is extruded at a steady rate to be charged.…”
Section: Introductionmentioning
confidence: 99%
“…These properties can support cell synthesis of specific proteins and other biochemical and biological processes required for healthy tissue growth [28,83]. Therefore, electrospun fibers have become excellent candidates for various applications, such as catalysis [84], filtration [85], water treatment [86][87][88][89], biosensors [90][91][92], food packaging [93,94], cosmetics [95] and biomedicine [96][97][98][99][100][101].…”
Section: Introduction Of Electrospinning Technologymentioning
confidence: 99%
“…Electrospinning is one of the powerful methods for continuous production of drug loaded nanofibers ( Xue et al, 2019 ; Liu et al, 2022a ; Sivan et al, 2022b ; Cao et al, 2022 ; Han et al, 2022 ; Lv et al, 2022 ), and electrospun nanofibers have been demonstrated their potential applications in almost all kinds of scientific fields such as energy, environment, medical and food ( Pang et al, 2021 ; Jiang et al, 2022a ; Li et al, 2022a ; Bai et al, 2022 ; Xu et al, 2022 ; Yu et al, 2023 ). As a top-down technology, electrospinning is famous for its simplicity, efficiency and flexibility in direct preparation of nanofibers ( Du et al, 2022 ; Huang et al, 2022 ; Yao et al, 2022 ). At present, there are many researches using electrospinning as a tool to construct medicated nanofibers ( Huang et al, 2021 ; Peng et al, 2021 ; El-Shanshory et al, 2022 ; Hameed et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%